Slotted waveguide array antennas : theory, analysis and design - Josefsson, Lars, 1939-; Rengarajan, Sembiam R., 1948- (Mario Boella series on electromagnetism in information & communication., 2018)
"Slotted waveguide antenna arrays are used in radar, communication and remote sensing systems for high frequencies. They have linear polarization with low cross-polarization and low losses but can also be designed for dual polarizations and phase steered beams. Slotted Waveguide Array Antennas is the first comprehensive treatment of these antennas from an engineering perspective. It provides readers with a thorough foundation in applicable theories as well as hands-on instruction for practical analysis, design, manufacture and use of important types of waveguide slot arrays. It goes beyond some of the commonly discussed topics and ventures into areas that include higher order mode coupling and edge effects; performance optimisation in terms of bandwidth and pattern performance and manufacturing tolerances. With specific examples of waveguide array designs, accompanied by detailed illustrations and antenna characteristics, the book is a must-have reference for engineers involved in antenna design, development and applications."--IET Digital Library